Turn in Teacher Training in Dominican Republic: Progress or Retrogress in this Reform? A Look from Human Rights - Florentino Morillo, Basilio (2021)
The essay analyzes the current reform of teacher training implemented in the Dominican Republic. It dispenses with content related to society’s legislation. This amendment promoted by the Ministry of Higher Education, Science, and Technology, which eliminates the subject on educational legislation, departs from the mandate of the Universal Declaration of Human Rights, the Constitution of the Republic, the Law of Higher Education, Science and Technology, the General Law of Education, and the same spirit of the regulations that legalize said reform. A change of this nature leads to the generation of a deficit in citizen training, social coexistence, and democracy. Consequently, the Dominican society could be entering a probable distance from the construction of a social state of rights, where citizens know, defend, and practice their privileges and fulfill their duties.